CD4 + primary cutaneous small/medium-sized pleomorphic T-cell lymphoma: a retrospective case series and review of literature. Issue 4 (April 2015) - James, Edward; Sokhn, Joseph G.; Gibson, Juliet Fraser; Carlson, Kacie; Subtil, Antonio; Girardi, Michael; Wilson, Lynn D.; Foss, Francine
Abstract CD4 + primary cutaneous small/medium-sized pleomorphic T-cell lymphoma (CD4 + PCSM-TCL) is a rare T-cell lymphoma associated with a favorable prognosis. A retrospective study of 23 patients with CD4 + PCSM-TCL as defined by World Health Organization–European Organisation for Research and Treatment of Cancer (WHO-EORTC) and WHO classifications was conducted. Median age was 63 years. The head and neck were the most commonly affected locations, followed by the trunk. Two patients had evidence of systemic involvement at relapse. All tumors were CD3 + and CD4+. CD5 and CD7 loss occurred in 52% and 84%, respectively. The median follow-up was 33.6 months. Eleven patients had excisional biopsy only, six had localized radiotherapy and two received excision and localized radiation. Cytotoxic chemotherapy and localized radiation were used in one patient with aggressive and invasive features. All patients had a complete remission but one developed systemic involvement. Our case series demonstrates that CD4 + PCSM-TCL is an indolent T-cell lymphoma that can be treated with local modalities and raises the question of its current classification as a lymphoma.